IDDF2019-ABS-0188 Gut microbiota modulates the chemopreventive efficacy of aspirin on colorectal cancer through impact on aspirin bioavailability. (June 2019) - Zhao, Risheng; Coker, Olabisi; Wu, Jianlin; Zhao, Liuyang; Nakatsu, Geicho; Bian, Xiqing; Sung, Joseph; Chan, Francis; El-Omar, Emad
Abstract : Background: The gut microbiota, a pivotal regulator in colorectal cancer (CRC) development, is profoundly involved in drug metabolism. This study aims to decipher the role of the gut microbiota in aspirin-mediated chemoprevention of CRC in mice. Methods: Two models, azoxymethane (AOM, 10 mg/kg) and dextran sulfate sodium (DSS, 2.0%) induced CRC and APC min/+ induced CRC, were used in this study. Mice were orally administered aspirin (400 mg/L) with or without periodical antibiotics cocktail (0.1 g/L of vancomycin, 0.2 g/L of ampicillin, metronidazole and neomycin). AOM/DSS-treated germ-free mice and conventionally reared germ-free mice (conventionalized mice) were used for validation. Aspirin concentration was estimated by ultra-high performance liquid chromatography (UHPLC). Aspirin-degrading microbes were identified by UHPLC and16S rRNA gene sequencing. Results: The tumor number and load were significantly reduced after aspirin treatment in antibiotics-treated mice in both AOM/DSS-treated and APC min/+ models, but not significantly changed in non-antibiotics-treated mice. Consistently, aspirin-treated germ-free mice exhibited significantly less tumor number and load compared to those not receiving aspirin, which was not seen in conventionalized mice, suggesting that gut microbiota impairs the chemopreventive efficacy of aspirin on CRC. UHPLC analysis revealed that plasma levels of aspirin were significantly higher in microbiota-depleted mice compared to microbiota-intact mice, indicating that gut microbiota limits aspirin bioavailability. Co-incubation of aspirin-containing medium and bacteria showed that aspirin levels in medium were significantly reduced when incubated with the fecal commensal bacteria from microbiota-intact mice compared to those from microbiota-depleted mice. Screening 1, 093 bacterial colonies isolated from the feces of microbiota-intact mice revealed that Lysinibacillus sphaericus significantly reduced the aspirin levels in aspirin-containing medium. Moreover, the germ-free mice monocolonized with Lysinibacillus sphaericus showed significantly lower plasma aspirin levels post aspirin administration relative to the intact germ-free mice, confirming a role of this bacterium in reducing aspirin bioavailability. Conclusions: Gut microbiota modulates the chemopreventive efficacy of aspirin on CRC through impact on aspirin bioavailability in mice. Lysinibacillus sphaericus may play a critical role in aspirin degradation in the gut.